Quantitative Assessment of Microalgae Biomass and Lipid Stability Post-Cultivation - Napan, Katerine; Christianson, Tyler; Voie, Kristen; Quinn, Jason C. (Frontiers in Energy Research, 2015)
Processing of microalgal biomass to biofuels and other products requires the removal of the culture from a well-controlled growth system to a containment or preprocessing step at non-ideal growth conditions, such as darkness, minimal gas exchange, and fluctuating temperatures. The conditions and the length of time between harvest and processing will impact microalgal metabolism resulting in biomass and lipid degradation. This study experimentally investigates the impact of time and temperature on Nannochloropsis salina harvested from outdoor plate photobioreactors. The impact of three temperatures, 4°, 40° or 70°C, on biomass and lipid content (as fatty acid methyl esters) of the harvested microalgae was evaluated over a 156 hour time period. Results show that for N. salina, time and temperature are key factors that negatively impact biomass and lipid yields. The temperature of 70°C resulted in the highest degradation with the overall biofuel potential reduced by 30% over 156 hours. Short time periods, 24 hours, and low temperatures are shown to have little effect on the harvested biomass.